Analisis Framing Pemberitaan Media Online CNN Indonesia.com dan Kompas.com terhadap Kasus Sidang Mahkamah Konstitusi, Bawaslu DKI Mengenai Pelanggaran Pemilu 2024 - Sihite, Ananda Sri Rezeki; Vallenxia Sijabat, Nanda Viola; Rohma, Putri Nailatur (Tuturlogi: Journal of Southeast Asian Communication, 2024)
This research aims to find out how the media frames and constructs news about the MK Session Case, DKI Bawaslu Against Election Violations in 2024 at kompasnews.com, and CNN Indonesia. this research uses the framing analysis method Framing analysis is used to identify and understand the point of view, focus, and use of language and images used in news. The data analyzed included quotes, titles, and images in both online media. The results of this analysis are expected to provide a better understanding of how CNN Indonesia.com and Kompas.com framed the news about the 2024 election violations in Bawaslu DKI and the Constitutional Court hearing. In addition, the results of this analysis can also identify differences and similarities in news framing between the two media. In addition, the results of this analysis can have an impact on the public's understanding and perception of the case.